Digitalisation and Modernisation of Hydropower Operating Facilities to Support the Colombian Energy Mix Flexibility - Aldemar Leguizamon-Perilla; Juan S. Rodriguez-Bernal; Laidi Moralez-Cruz; Nidia Isabel Farfán-Martinez; César Nieto-Londoño; Rafael E. Vásquez; Ana Escudero-Atehortua (Energies, 2023)
Hydropower plants cover almost 70% of the Colombian electrical demand, were built several decades ago, and present low levels of digitisation compared to other modern power-generation technologies, e.g., wind turbines, solar PV plants, and recently buil hydroelectric plants t. Renovating power plant equipment and investing in modernisation and digitisation can significantly increase the plant flexibility. Those actions will increase a plant’s operational safety and contribute to the solution of environmental and social problems. This work presents the actions followed to extend the lifetime of a 1000 MW hydropower plant operating for more than 40 years. Activities included a residual life status evaluation of generators and component upgrades, among others. The rehabilitation and digitalisation of the generation units allow their integration and remote monitoring so that diagnostic actions can be carried out during a continuous and economically sustainable operation. These activities complement the plan implemented by the company during the last decade to ensure the plant’s operation for another 50 years and its respective integration with nonconventional generation systems at the national level. Besides the generator’s life extension, the main result of rewinding is an increase in the Minimum Breakdown Voltage by almost 140% (from 38.4 kV to 95.6 kV) with respect to the current operation state, ensuring its operation for the following years.